Hydroxyapatite bone cement in the reconstruction of defects of the long process of the incus: Personal experience and literature review - Mantsopoulos, Konstantinos; Thimsen, Vivian; Wohlleben, Felix; Sievert, Matti; Müller, Sarina Katrin; Goncalves, Miguel; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2021)
Objective: Erosion of the long process of the incus is the most common ossicular chain pathology occurring in the course of chronic middle ear disease. The aim of this study was to evaluate our experience in the reconstruction of short-length defects of the long process of the incus using hydroxyapatite bone cement over a period of 15 years. Methods: The medical records of all patients treated with hydroxyapatite bone cement for an isolated short-length erosion of the long process of the incus or the lenticular process at an academic tertiary referral center between 2005 and 2019 were studied retrospectively. Results: 48 patients made up our study sample (19 men, 29 women). The mean age at the time of surgery was 38.1 years. The mean preoperative air-bone gap (ABG) was 21.36 dB. The mean postoperative ABG was 15.89 dB within 8 weeks of surgery and 11.81 dB at least 6 months after surgery. The postoperative ABG had significantly improved compared to preoperative ABG values at both the short- and middle-term follow-up (p < 0.001 for both). An ABG ≤ 20 dB was achieved in 68% in the short term and 83% in the middle term. The mean ABG in the long term (< 12 months) was 11.1 dB. Conclusion: Restoration of the anatomic and functional continuity of the ossicular chain using hydroxyapatite cement in defects of the long process of the incus seems to warrant a satisfactory audiologic outcome in the majority of cases.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Bone cement; Hydroxyapatite; Incus; Long process; Ossicular chain